PEMAAFAN HAKIM DALAM HUKUM PIDANA INDONESIA : PESPEKTIF FALSAFAH PANCASILA - Ariyad, Fikri; Islamy, Athoillah (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2022)
This study intends to identify the values of the Pancasila philosophy in the concept of forgiveness of judges contained in the Draft Criminal Code (RKUHP). This study uses a normative-philosophical approach. The data analysis technique is through the stages of data reduction, data presentation, and data verification. The results of the study show that there are dimensions of the values of the Pancasila philosophy in the concept of forgiveness of judges. Those values are the divinity value, humanity value, national value, democracy value, justice value. The theoretical implication of this research shows that the various values of Pancasila can be the basis of legal paradigms and ideals in the modernization of Indonesian criminal law so that they are in line with the spirit of Indonesian values. The limitation of this research is that it has not reviewed the formal legal provisions of the concept of judge forgiveness